Reputation management : the future of corporate communications and public relations - Langham, Tony (Company founder) (Emerald Publishing Limited, 2018)
A good reputation is vital to success in business and in life. Organisations with the best reputations outperform rivals in a myriad of tangible ways; they recruit higher quality staff, succeed with smaller marketing budgets, and exert greater influence over Governments. Although in the long term reputation is based on reality and behaviour, short term examples of organisations and individuals building unfair advantage can be seen all around us. Despite this, reputation remains an often misunderstood and neglected asset. In' Reputation Management: The Future of Corporate Communications and Public Relations', Tony Langham argues that reputation management is the future incarnation of public relations and corporate communications. Featuring specially commissioned essays, as well as exclusive interviews with leading CEOs, influencers and celebrities, the book covers issues as diverse as fake news, AI, James Bond, cyber security and internet bullying. Also included are contributions from thirty-nine of the world's leading reputation managers who exclusively reveal the time they made the most difference to an organisation's reputation. 'Reputation Management' provides a complete blueprint and toolkit for reputation management and is essential reading for CEOs, Board Directors and shareholders in businesses who ultimately bear the responsibility and costs of reputation management. It will also prove indispensable to all professionals and students working in or studying business, marketing, corporate communications and public relations.
Prelims -- What is reputation? -- What makes a great reputation? -- The value of reputation -- Measuring reputation (and the current state of play) -- Managing reputation -- Perspectives on reputation management -- Gender, diversity and reputation management -- The reputation management toolkit -- Case studies from the best of the best -- Crisis management -- The forces shaping reputation today -- Reputation management in future -- Postscript: reputation management, a force for Good? -- Endnotes -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Public relations; Communication in organizations; Business & Economics -- Industries / Media & Communications; Media, information & communication industries